2006
DOI: 10.3892/ijo.28.1.261
|View full text |Cite
|
Sign up to set email alerts
|

RANKL directly induces bone morphogenetic protein-2 expression in RANK-expressing POS-1 osteosarcoma cells

Abstract: Abstract. The POS-1 murine model of osteolytic osteosarcoma was used to elucidate the molecular and cellular mechanisms involved in the development of primary bone tumors and associated lung metastasis. The POS-1 cell line is derived from an osteosarcoma tumor which develops spontaneously in C3H mice. The POS-1 cell line was characterized in vitro by mineralization capacity and expression of bone markers by semi-quantitative RT-PCR, compared to primary osteoblasts and bone marrow cells. POS-1 cells showed no m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…However its expression is not restricted to this cell type, as it was also observed in other tissue including mammary gland [29], lung [20], brain [20], kidney [20] and hypertrophic chondrocytes [15]. Recently, functional RANK expression on tumor cells was reported by our laboratory [21] and others [22,30]. Indeed, we have recently reported the expression of functional RANK in POS-1 mouse osteosarcoma cells [21].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However its expression is not restricted to this cell type, as it was also observed in other tissue including mammary gland [29], lung [20], brain [20], kidney [20] and hypertrophic chondrocytes [15]. Recently, functional RANK expression on tumor cells was reported by our laboratory [21] and others [22,30]. Indeed, we have recently reported the expression of functional RANK in POS-1 mouse osteosarcoma cells [21].…”
Section: Discussionmentioning
confidence: 91%
“…RANK expressed on osteoclast/osteoclast precursors has been largely described as a key receptor that control osteoclast differentiation, activity and survival [12,14,15,20]. However, we and others have demonstrated the expression of functional RANK at the surface of tumor cells that develop in bone, including a mouse osteosarcoma cell line, POS-1 [21,22]. These recent findings bring new insights in the vicious cycle theory between bone resorbing cells and cancer cells [23].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, recent studies found that functional RANK was expressed in some primary and some secondary bone tumors, including osteosarcoma (5,6), chondrosarcoma (7), breast cancer (8), prostate cancer (9,10), renal cell cancer (11) and malignant melanoma (8). RANKL can promote cancer cell migration and invasion in in vitro experiments, and induce osteoclast chemotaxis (7,10,12).…”
Section: Introductionmentioning
confidence: 99%
“…After reaching 70 -80% confluence, cells were treated for 6 h with 100 ng/ml human sRANKL (PeproTech) to induce Bmp2 expression (35). Mouse F9 embryonal carcinoma cells were maintained and induced to differentiate as described previously (18).…”
Section: Methodsmentioning
confidence: 99%